De novo transcriptome assembly and genome annotation of the fat-tailed dunnart (Sminthopsis crassicaudata) - Ibeh, Neke; Feigin, Charles Y.; Frankenberg, Stephen R.; McCarthy, Davis J.; Pask, Andrew J.; Gallego Romero, Irene (GigaByte (Hong Kong, China), 2024)
Marsupials exhibit distinctive modes of reproduction and early development that set them apart from their eutherian counterparts and render them invaluable for comparative studies. However, marsupial genomic resources still lag far behind those of eutherian mammals. We present a series of novel genomic resources for the fat-tailed dunnart (Sminthopsis crassicaudata), a mouse-like marsupial that, due to its ease of husbandry and ex-utero development, is emerging as a laboratory model. We constructed a highly representative multi-tissue de novo transcriptome assembly of dunnart RNA-seq reads spanning 12 tissues. The transcriptome includes 2,093,982 assembled transcripts and has a mammalian transcriptome BUSCO completeness score of 93.3%, the highest amongst currently published marsupial transcriptomes. This global transcriptome, along with ab initio predictions, supported annotation of the existing dunnart genome, revealing 21,622 protein-coding genes. Altogether, these resources will enable wider use of the dunnart as a model marsupial and deepen our understanding of mammalian genome evolution.